(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
Marek’s disease is a highly contagious, immunosuppressive, lymphotropic, and economically effective illness of avian species, mainly chickens, caused by a herpes virus known as Gallid herpesvirus 2 of the subfamily Alphaherpesvirinae. In this study, the prevalence of Marek’s disease in different Iraqi governorates was investigated using highly specific and sensitive primers. The results revealed that twelve farms out of the total 50 tested were positive for Marek’s virus representing 24%. The highest rate of infected farms was recorded in Baghdad with 4 farms (23.5%) followed by Diyala, Wasit, and Karbala at infection rates of 2(25%), 3(27.3%), and 3(100%) farms respectively. In addition, the study showed that the infection was recorded in two time periods during the study duration: the first one from February through April, and the second one from August through November. The affected bird’s age was also analyzed, with an inconclusive rate. In conclusion, this study provides molecular evidence of Marek’s disease circulation within Iraqi poultry farms even under a vaccine control strategy.